PENGARUH EVALUASI PEMBELAJARAN BERBANTUAN WORDWALL TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SD NEGERI 026606 BINJAI BARAT TAHUN AJARAN 2025/2026 - Nadila Khoiru Wannafa; Masta Marselina Sembiring; Eva Betty Simanjuntak; Dody Feliks Pandimun Ambarita; Natalia Silalahi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effect of Wordwall-assisted learning evaluation on the reading comprehension skills of fourth-grade students at SD Negeri 026606 Binjai Barat in the 2025/2026 academic year. This study employed a Quasi-Experimental Design with a Nonequivalent Control Group Design. The population consisted of all fourth-grade students at SD Negeri 026606 Binjai Barat. The sample was selected using a saturated sampling technique and consisted of 17 students in the experimental class and 15 students in the control class. The research instrument was a multiple-choice reading comprehension test. The results of the instrument analysis showed that, out of 30 items tested, 22 items met the criteria of validity, reliability, item difficulty, and discrimination power. Subsequently, 20 items were selected as the research instrument by considering the representation of reading comprehension indicators at the cognitive levels of C3, C4, and C5, as well as the effectiveness of the test administration time. The results showed that the average reading comprehension score of students in the experimental class increased from 57.35 to 82.05, while the average score in the control class increased from 51.67 to 60.33. The normality test indicated that the pretest and posttest data of both the experimental and control classes were normally distributed, as all significance values were greater than 0.05. The homogeneity test showed that the pretest and posttest data had homogeneous variances, with significance values of 0.539 and 0.092, respectively. The hypothesis testing using simple linear regression analysis obtained a significance value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. Furthermore, the coefficient of determination (R Square) was 0.711, indicating that 71.1% of students' reading comprehension skills were influenced by Wordwall-assisted learning evaluation, while the remaining 28.9% were influenced by other factors not examined in this study. The regression analysis produced the equation Y = 60.333 + 21.725X, indicating that Wordwall-assisted learning evaluation had a positive effect on students' reading comprehension skills. Therefore, it can be concluded that Wordwall-assisted learning evaluation has a positive and significant effect on the reading comprehension skills of fourth-grade students at SD Negeri 026606 Binjai Barat in the 2025/2026 academic year.